2020
DOI: 10.5194/nhess-20-3439-2020
|View full text |Cite
|
Sign up to set email alerts
|

A classification scheme to determine wildfires from the satellite record in the cool grasslands of southern Canada: considerations for fire occurrence modelling and warning criteria

Abstract: Abstract. Daily polar-orbiting satellite MODIS thermal detections since 2002 were used as the baseline for quantifying wildfire activity in the mixed grass and agricultural lands of southernmost central Canada. This satellite thermal detection record includes both the responsible use of fire (e.g. for clearing crop residues, grassland ecosystem management, and traditional burning) and wildfires in grasslands and agricultural lands that pose a risk to communities and other values. A database of known wildfire e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…With a warming climate, there is a risk of increasing peatland and "legacy carbon" fires (Ingram et al, 2019) in boreal forests, particularly in stands younger than 60 years where drying limits the resilience of the carbon-rich soils (Walker et al, 2019), and in drying fen watersheds near large settlements, like the costliest wildfire in Canada's history -the May 2016 Horse River-Fort McMurray fire (Elmes et al, 2018). Future emission estimates from peat fires will need to be informed by where and in what condition these carbonrich soils reside, particularly as predicted moderate and severe drought in boreal peatlands in western Canada are expected to increase fire size by over 500 % (Thompson et al, 2019). Current Earth system models do not typically characterize well or include peat fires and related feedbacks (Lasslop et al, 2019;Loisel et al, 2020), further limiting our ability to predict future emissions from peatland burning.…”
Section: Peatlandsmentioning
confidence: 99%
“…With a warming climate, there is a risk of increasing peatland and "legacy carbon" fires (Ingram et al, 2019) in boreal forests, particularly in stands younger than 60 years where drying limits the resilience of the carbon-rich soils (Walker et al, 2019), and in drying fen watersheds near large settlements, like the costliest wildfire in Canada's history -the May 2016 Horse River-Fort McMurray fire (Elmes et al, 2018). Future emission estimates from peat fires will need to be informed by where and in what condition these carbonrich soils reside, particularly as predicted moderate and severe drought in boreal peatlands in western Canada are expected to increase fire size by over 500 % (Thompson et al, 2019). Current Earth system models do not typically characterize well or include peat fires and related feedbacks (Lasslop et al, 2019;Loisel et al, 2020), further limiting our ability to predict future emissions from peatland burning.…”
Section: Peatlandsmentioning
confidence: 99%
“…While a strong effect of phenology on fire proneness is expected in areas that are both subjected to a high degree of human land use and have a large proportion of broadleaf forest cover, as exemplified in the BP ecozone, this fire–phenology association may be partially conflated with other environmental factors. For instance, at the southern fringe of the boreal biome in western Canada, human‐caused ignitions associated with agricultural activities, whether deliberate or accidental, are common in the spring (Thompson & Morrison, 2020). Occasionally, a springtime ignition develops into a large conflagration that burns for weeks or months, though large springtime wildfires are not as prevalent as those burning during the summer in Canada (Burton et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Parfenova et al (2019) found crop growing conditions would be established in some of the permafrost zones of Siberia under RCPs 2.6 and 8.5 by 2080, favorable for wheat and maize (silage) production. These crops are commonly managed via open burning practices in the U.S., eastern Europe, Russia, and Canada (Kutcher and Malhi, 2010;McCarty et al, 2017;Theesfeld and Jelinek, 2017;Shiwakoti et al, 2019;Thompson and Morrison, 2020). Thus, seasonality of burns and management of croplands, grasslands, and deciduous forests may occur at times when transport of emissions to the Arctic is likely, i.e., late winter/early spring for Russia (Hall and Loboda, 2018;Qi and Wang, 2019) and Canada and north central U.S. (Viatte et al, 2015), respectively.…”
Section: Fire Management In the Arcticmentioning
confidence: 99%